Data Resource Profile: Maternity Services Dataset (MSDS) - Stewart, Catherine; Hall, Jennifer; Harron, Katie (International Journal of Population Data Science, 2026)
Introduction The Maternity Services Dataset (MSDS) is a comprehensive administrative dataset, capturing detailed information on NHS-funded maternity services in England. It encompasses the full maternity care pathway. There are two versions of the dataset: MSDS V1.5, introduced in May 2015, and the updated MSDS V2.0, which replaced it in April 2019. Methods MSDS is a secondary-use dataset, repurposing clinical and operational data primarily for monitoring, commissioning, and auditing purposes. Data is submitted monthly by trusts, enabling NHS England to generate a national picture of maternity activity and publish official statistics. Patient identifiers enable linkage with other NHS datasets, such as Hospital Episode Statistics (HES). Results The dataset includes demographic, clinical, and organisational information for each pregnant person and their baby, such as appointment dates, diagnoses, delivery details, birthweight, and neonatal admissions. Provider and geographical data are also recorded. Data quality varies due to the classification of variables as mandatory, required, or optional. Most variables are required, meaning submission is expected when applicable, but not enforced, leading to inconsistencies in data completeness across trusts. Only a small number of fields are mandatory, meaning that data must be present for a successful submission. Conclusions The MSDS is used for national and local health service planning, including major audits such as the National Maternity and Perinatal Audit. Although it holds potential for research, uptake has been limited to date due to its relative novelty. As coverage improves and the number of available years increases, the MSDS will become an increasingly robust resource for conducting research. It contains a wealth of information from the maternity services pathway - much of which is not available elsewhere - making it a highly valuable dataset for pregnancy-related research. Access to the MSDS is provided by NHS England. Data are requested through the online Data Access Request Service.